Hepatocellular carcinoma in patients with chronic renal disease: Challenges of interventional treatment. (March 2021) - Sarno, Gerardo; Montalti, Roberto; Giglio, Mariano Cesare; Rompianesi, Gianluca; Tomassini, Federico; Scarpellini, Emidio; De Simone, Giuseppe; De Palma, Giovanni Domenico; Troisi, Roberto Ivan
Abstract: Hepatocellular carcinoma (HCC) is a common malignancy worldwide, recognized as the fourth most common cause of cancer related death. Many risk factors, leading to liver cirrhosis and associated HCC, have been recognized, among them viral hepatitis infections play an important role worldwide. Patients suffering from chronic kidney disease (CKD), especially those on maintenance dialysis, show a higher prevalence of viral hepatitis than the general population what increases the risk of HCC onset. In addition, renal dysfunction may have a negative prognostic impact on both immediate and long-term outcomes after malignancy treatment. Several interventional procedures for the treatment of HCC are currently available: thermal ablation, transcatheter arterial chemoembolization, liver surgery or even liver transplantation. The Barcelona Clinic Liver Cancer system provides an evidence-based treatment algorithm to address different categories of patients to the most-effective treatment in consideration of the extension of disease, liver function and performance status. Liver resection and transplantation are usually reserved to patients with early stage HCC and acceptable performance status, while the other treatments are more indicated in case of impaired liver function or locally advanced or unresectable tumors. However, there is no validated treatment algorithm for HCC in CKD patients, mainly due to the rarity of reports in this cohort of patients. Hereby we discuss the available evidences on interventional HCC treatments in CKD patients, and briefly report up-to-date pharmacological therapy for HCC patients affected by viral hepatitis.